Analisis Sudut Pandang Kamera Dan Jenis Kamera - Triyono Triyono; M. Ardy Hariwibowo; Bian Pramana Putra (UNIVERSITAS RAHARJA, 2016)
The development of computer technology in particular fields of multimedia, visual and audio broadcasting already very rapidly growing at this time as well as the extent of the need for information on the society, the more recent contributions in presenting the image capture, the camera is the most popular tool in photography. The name is derived from the camera obscura, Latin for